Synthesis and some properties of Al4SiC4-Al4O4C composites. Issue 14 (1st October 2018) - Yu, Chao; Cheng, Keren; Ding, Jun; Zhu, Hongxi; Deng, Chengji; Bai, Chen
Abstract: Al4 SiC4 -Al4 O4 C composites were prepared by using aluminum, silica and graphite as starting raw materials. Several factors including the synthesis temperature and ratio of raw materials were determined and the impacts on the formation process and morphology of Al4 SiC4 -Al4 O4 C composites were investigated. Two steps including solid-liquid and solid-solid reactions proceed successively during the formation of Al4 SiC4 -Al4 O4 C. The optimum conditions for synthesizing were sintered at 1700 °C for 2 h. Al4 SiC4 -Al4 O4 C composites were observed to be oxidized at temperatures around 800 °C. A layer of Calcium hex aluminate (CA6) formed on the hot face of the Al4 SiC4 -Al4 O4 C as corrosion proceeded, resulting in a significant decrease in the rate of melting slag erosion.